Log periodic dipole array antenna for UHF band application / Shazrol Basri - Basri, Shazrol (2010)
The Ultra High Frequency (UHF) band has long been used for voice, data and video communication. The upper frequency band of the UHF which is the 0.3 - 3GHz is used for terrestrial TV broadcast and WLAN system. The conventional UHF antennas for receiving TV signals are quite large and directional. So it would be better to have a compact and omnidirectional antenna that can be easily fabricated and efficient. Log Periodic Dipole Array antenna is one example of antenna with smaller size and good response. The antenna was designed to operate from 2 - 4GHz to cover the standard frequency of IEEE 802.11 b/g (2.4-2.4835GHz), WiMAX (2.3-3.6GHz) and Wi-Fi of 2.4GHz band. The dipole antenna is one of the omnidirectional that can be easily designed. The planar type of antenna is one of the easiest to fabricate. In this work, the design is made using a linear planar dipole scheme. The simulation process was done using the Computer Simulation Technology CST Microwave Studio while the measurement processes were accomplished with the aid of Vector Network Analyzer (VNA) software. The antenna has been fabricated on the FR4 microstrip board with er = 4.9 and thickness of 1.6 mm using the photolithography and wet etching technique. Return loss results of the fabricated design have a value of approximately -18dB with a bandwidth of 45%, which could be considered as a wider bandwidth.